Anti-Racist Pedagogy in the Canonization of Toni Morrison - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
The paper aims to examine the anti-racist approach in pedagogy in relation to the issues of representations of African Americans in American schools, curricula, and literary canon. It has considered anti-racist pedagogy as a correct approach to creating a truly democratic society in a racist society like the United States of America. In order to address these issues, Toni Morrison has been considered the most successful African American writer who has attained canonical status within the mainstream of both African American and American literature. The paper has, thus, raised some of the vital issues related to the representations of African Americans in American schools, curricula, and the literary canons. Crossing the Border: International Journal of Interdisciplinary Studies 5(2) 2017: 15-24